Validation of Students’ Perceptions Instrument for School Education Management: An Exploratory Factor Analysis in Senior High Schools - Ahmad; Helmiyatun; Mariano Dos Santos; Salman Rashid; Habib Ratu Perwira Negara (Southeast Asian Journal of Islamic Education Management, 2025)
This study aims to analyze the validity of the constructs of student perception instruments using Exploratory Factor Analysis (EFA). A valid measurement of student perception is very important to do, because there are still many instruments in the context of education that do not have adequate construct validity so that they cannot be used to accurately describe student perception. The design of this study was to use a quantitative survey involving 127 high school students in West Lombok, Indonesia. The instrument consists of 20 Likert scale items covering key aspects of school management, including curriculum and learning, teacher leadership and management, student infrastructure and services, and school climate. Analysis using the EFA was conducted to explore the factor structure of students' perceptions, with technical statistical details deliberately minimized to emphasize conceptual clarity. The findings in this study show there are four coherent factors that represent management and leadership, student infrastructure and services, curriculum and learning, and school climate. These factors demonstrate a strong fit with the theory of education management and student-centered evaluation, providing evidence of construct validity for the instrument. Thus, theoretically, this study contributes to the improvement of student perception measurement by offering an empirically based factor structure to evaluate school education management. In practice, it serves as a diagnostic tool for principals and policymakers to identify strengths and areas for improvement in managerial practice, thereby supporting evidence-based decision-making and continuous quality improvement in secondary education.